2018
DOI: 10.1111/tmi.13152
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions for unstable patients on antiretroviral therapy in South Africa: results of a cluster‐randomised evaluation

Abstract: Background As loss from HIV care is an ongoing challenge globally, interventions are needed for patients who don't achieve or maintain ART stability. The 2015 South African National Adherence Guidelines (AGL) for Chronic Diseases include two interventions targeted at unstable patients: early tracing of patients who miss visits (TRIC) and enhanced adherence counselling (EAC). Methods As part of a cluster‐randomised evaluation at 12 intervention and 12 control clinics in four provinces, intervention sites implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
(39 reference statements)
3
21
1
Order By: Relevance
“…A study from Zimbabwe found that patients undergoing three sessions of enhanced adherence counselling were more likely to resuppress compared to non‐attendance to enhanced counselling (relative risk of resuppression 2.8, 95% CI 1.8 to 4.2) . A study from South Africa found only a small benefit to EAC in terms of viral suppression within three months (8.1% increase compared to those not receiving EAC in adjusted analysis), and this difference was not sustained over 12 months .…”
Section: Discussionmentioning
confidence: 99%
“…A study from Zimbabwe found that patients undergoing three sessions of enhanced adherence counselling were more likely to resuppress compared to non‐attendance to enhanced counselling (relative risk of resuppression 2.8, 95% CI 1.8 to 4.2) . A study from South Africa found only a small benefit to EAC in terms of viral suppression within three months (8.1% increase compared to those not receiving EAC in adjusted analysis), and this difference was not sustained over 12 months .…”
Section: Discussionmentioning
confidence: 99%
“…While optimum strategies are not well known, these may include improved access to self-testing [51], use of incentives [8], and male-friendly services that emphasize confidentiality and include flexible hours, integrated care, and reduced visit frequency [52,53], as well as decentralization of services such as through community adherence groups [1,8,51,54]. Furthermore, effective retention support mechanisms-such as undertaking early and intensive tracing among patients LTFU from ART services (as soon as 1 week after loss to follow-up) via phone calls, text messages, or community visits-may be an important strategy towards improving HIV outcomes among men, but require further study [55][56][57][58][59][60][61]. The recently published SEARCH Study may provide clues as to how better to reach and retain men [62].…”
Section: Plos Medicinementioning
confidence: 99%
“…Efforts should be intensified to identify patients at risk of poor adherence, and establish the support that is needed to overcome the most important barriers to adherence [41]. Enhanced adherence counselling alone, however, may not provide sufficient additional support than the current standard of care [42] and several successful interventions have been used to improve adherence and viral suppression [43,44]. This includes regimen simplification [45], use of single-tablet regimens [46], short message service (SMS) text messages [47], and communitybased ART programs [48,49].…”
Section: Plos Onementioning
confidence: 99%
“…This includes regimen simplification [45], use of single-tablet regimens [46], short message service (SMS) text messages [47], and communitybased ART programs [48,49]. Although adherence intensification is likely to increase the probability of re-suppression on the same regimen, this does not always hold true [42,50,51]. Resistance testing, where feasible, has been proposed for those with higher levels of viremia at failure to improve discernment between patients in need of a switch to second-line therapy versus those in need of adherence support interventions [51].…”
Section: Plos Onementioning
confidence: 99%